Analisis Hukum Pajak Bea Cukai terhadap Barang-Barang Bawaan Tenaga Kerja Indonesia Perspektif Peraturan Menteri Keuangan Nomor 141 Tahun 2023 dan Al-Maslahah - Fajar Mahalim Harahap; Zaid Alfauza Marpaung (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The phenomenon of labor migration, particularly Indonesian Migrant Workers (TKI), is a complex socio-economic issue in Indonesia. Migrant workers contribute significantly to the country's foreign exchange through remittances, but they face various challenges, including customs regulations when bringing goods back to the country. This study aims to analyze the Customs Tax on Goods Carried by Indonesian Workers from the perspective of the Minister of Finance Regulation Number 121 of 2023 and Al masalahah. And this type of research uses normative legal research whose sources of primary, secondary, tertiary legal materials are collected and analyzed qualitatively. This study concludes that to overcome this problem, the Indonesian government issued PMK Number 141 of 2023, which aims to provide convenience and legal certainty for migrant workers in carrying their luggage. This regulation regulates the exemption of import duties for certain goods and is expected to simplify the customs process and improve protection for migrant workers. Although this PMK makes a positive contribution, it still needs better evaluation and socialization to ensure effective implementation in the field. This research also examines Al-Maslahah values in the context of tax and customs policies, with the hope of creating justice and welfare for migrant workers.